Efektivitas Pemutihan Pajak Kendaraan Bermotor Pada Masa Pandemi - Ni Made Darmakanti; Ni Kadek Ema Sri Febriyanti (Jurnal Pacta Sunt Servanda, 2021)
Taxes are a source of state revenue and revenue that aims to improve national development and improve people’s welfare. Texas can also be interpreted as a source of state revenue for the implementation of government and development activities as well as a driving force for economic activity. Therefore, the tax sector plays and important role in the development of the nation’s welfare. Taxpayers must fulfill their obligations in making tax payments, however currently tax collection one of which is that vehicle taxes are difficult to to due to lack of public awareness, especially when this is coupled with the Covid-19 pandemic. Due to the delays in paying taxes by the pandemic, thus has resulted in a tax bleaching policy on vehicles in the form of bleaching.